2015
DOI: 10.1182/blood-2014-09-603217
|View full text |Cite
|
Sign up to set email alerts
|

Excessive antigen reactivity may underlie the clinical aggressiveness of chronic lymphocytic leukemia stereotyped subset #8

Abstract: Key Points• mAbs from aggressive CLL subset #8 display extreme antigen polyreactivity, in clear contrast with the mAbs from other aggressive CLL subsets.• Subset #8 CLL clones respond avidly to stimulation by multiple antigens and this may underlie their noted propensity to transform.Subset #8 is a distinctive subset of patients with chronic lymphocytic leukemia (CLL) defined by the expression of stereotyped IGHV4-39/IGKV1(D)-39 B-cell receptors. Subset #8 patients experience aggressive disease and exhibit the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 82 publications
(67 reference statements)
0
41
0
1
Order By: Relevance
“…IgD stimulation can cause CLL-cell apoptosis [125] or survival and plasma cell differentiation [126] and differential responsiveness to IgD stimulation has been linked to clinical outcome [127]. Although the nature of the antigens stimulating CLL-BCRs in patients is still poorly defined, some reports have shown that U-CLL BCRs are polyreactive and mostly recognize autoantigens and other environmental antigens [40, 128137] including cytoskeletal non-muscle myosin heavy chain IIA (MYHIIA), vimentin, cofilin-1, Fc tail of IgG, single-stranded DNA (ssDNA) or double-stranded DNA (dsDNA), lipopolysaccharide (LPS), apoptotic cells, oxidized low-density lipoprotein (ox-LDL), lupus-associated ribonuclear protein Smith (Sm), human immunodeficiency virus 1 and hepatitis C viral antigens and bacterial antigens (Figure 3). In contrast, affinity-matured BCRs from M-CLL cases bind to a restricted set of more specific antigens, including β-(1,6)-glucans from yeast and fungi [138] and the Fc tails of rheumatoid factors [131133, 139] (Figure 3).…”
Section: B-cell Receptor Signaling In Cllmentioning
confidence: 99%
See 1 more Smart Citation
“…IgD stimulation can cause CLL-cell apoptosis [125] or survival and plasma cell differentiation [126] and differential responsiveness to IgD stimulation has been linked to clinical outcome [127]. Although the nature of the antigens stimulating CLL-BCRs in patients is still poorly defined, some reports have shown that U-CLL BCRs are polyreactive and mostly recognize autoantigens and other environmental antigens [40, 128137] including cytoskeletal non-muscle myosin heavy chain IIA (MYHIIA), vimentin, cofilin-1, Fc tail of IgG, single-stranded DNA (ssDNA) or double-stranded DNA (dsDNA), lipopolysaccharide (LPS), apoptotic cells, oxidized low-density lipoprotein (ox-LDL), lupus-associated ribonuclear protein Smith (Sm), human immunodeficiency virus 1 and hepatitis C viral antigens and bacterial antigens (Figure 3). In contrast, affinity-matured BCRs from M-CLL cases bind to a restricted set of more specific antigens, including β-(1,6)-glucans from yeast and fungi [138] and the Fc tails of rheumatoid factors [131133, 139] (Figure 3).…”
Section: B-cell Receptor Signaling In Cllmentioning
confidence: 99%
“…U-CLL cells express BCRs specific for autoantigens, including non-muscle myosin heavy chain IIA (MYHIIA), vimentin, lupus associated ribonuclear protein Smith (Sm), single-stranded DNA (ssDNA), double-stranded DNA (dsDNA), oxidized low-density lipoprotein (oxLDL) as well as microbial antigens, including lipo-polysaccaride (LPS) [40, 128137]. U-CLL are generally highly responsive to antigenic stimulation [10, 120], as well as those expressing high levels of CD38 [10, 117] and ZAP70 [119].…”
Section: Figurementioning
confidence: 99%
“…10,[15][16][17][18][19][20][21][22][23][24][25] In addition, preliminary observations in CLL, in relatively small patient series, suggest that the frequency and patterns of mutations within several genes, namely, NOTCH1, SF3B1 and TP53, may differ amongst subsets of patients carrying stereotyped BcRs, the paradigmatic example being the recently observed enrichment of SF3B1 mutations in the clinically aggressive subset #2. [26][27][28] With this in mind, we sought to systematically evaluate the mutational status of BIRC3, MYD88, NOTCH1, SF3B1 and TP53 in 565 CLL patients assigned to one of 10 major stereotyped subsets, and representing cases with varying SHM status, i.e.…”
Section: Different Spectra Of Recurrent Gene Mutations In Subsets Of mentioning
confidence: 99%
“…Blood supply of neoplastic tumour condition inflow of glucose to cancer cells usually manifesting glycolytic metabolism [41], which represents an important stage in further development on the lesion. This results in a more rapid growth of the tumour and in presence of accompanying cells of chronic inflammatory process, macrophages and lymphocytes.…”
Section: Alterations In Tumor Microenvironmentmentioning
confidence: 99%